Dinamika Gender dalam Konteks Budaya Sunda di Kalangan Supporter Wanita Persib - Sya'rani, Ahmad Zaeri; Rizkia, Fikri (Jurnal Kepelatihan Olahraga, 2024)
This study examines gender dynamics in the context of Sundanese culture among female Persib Bandung supporters. Data was collected through in-depth interviews (direct, personal, and unstructured interviews) with 134 respondents. Based on the research results, the characteristics of female supporters are very diverse. The age of female supporters consists of under 17 years old 27%, 17-30 years old 43%, and over 30 years old 30%. The length of time supporting the favorite club starts from 1 year down 17%, 2-5 years 38%, 6-10 years 23%, and those above 10 years 22%. In addition, the decision to support soccer is motivated by various reasons such as purely from within, influence from parents and friends, and stress relief. Based on this research, there are gender stereotypes still felt by female supporters in supporting their favorite team. In addition, women are generally not associated with supporting soccer.